Dinamika Sikap Provos Menwa Mahadhipa Batalyon 914 Ganesha UKSW Terhadap Agresi Dalam Pembentukan Disiplin - Lezario Anantyas Basuki; Rudangta Arianti (Universitas Kristen Maranatha, 2021)
In the Resimen Mahasiswa (menwa), all members are obligated to comply to the rules. The disciplining tactis used in menwa’s training are often associated with aggressive behavior from the provosts to the juniors. These aggressive behaviors often cause the juniors to become victims, hence why most juniors decide to leave menwa. The purpose of this study is to determine the attitude of the Resimen Mahasiswa Satya Wacana Christian University's Provos 914 Battalion Mahadhipa towards aggression in their training. This research uses a qualitative research approach, with 2 provosts as research participants. The results of this study showed that different attitudes of the two participants will result in different internal responses which will form a certain belief. This belief can also form different results in the behavior of the two participants. On the other hand, different internal responses can also produce similar behavior.